A rare case report of hypertrophic cardiomyopathy induced by catecholamine-producing tumor - Olmati, Federica (Medicine (Baltimore), 2018)
RATIONALE: Catecholamine-producing tumors are rare, occurring in less than 0.2% of patients with hypertension, but can have relevant cardiovascular morbidity and mortality. PATIENT CONCERNS: A 37-year-old woman presented with a history of dyspnea, chest pain, palpitations, and paroxysmal hypertension. Electrocardiogram, echocardiogram, and cardiac magnetic resonance showed severe LVH with a prevalent involvement of the anterior portion of interventricular septum. Endomyocardial biopsy found severe hypertrophy with disarray of cardiomyocytes and ultrastructural evidence of contraction and necrosis of myocytes. Hormone investigations revealed high values of 24-hours urinary metanephrines. Abdominal computed tomography (CT) showed an enlarged left adrenal gland with a strong uptake of (123)I—metaiodobenzylguanidine at scintigraphy scan. INTERVENTIONS: Thus, the adrenal tumor was surgically removed. OUTCOMES: At follow-up examination, the patient's metanephrines levels were normalized and the transthoracic echocardiogram showed a reduction of LVH. DIAGNOSIS AND LESSONS: We report a rare case of catecholamine–induced cardiomyopathy due to an adrenal adenoma mixed with nodules enriched in epinephrine-types secreting granules.